2018
DOI: 10.1146/annurev-bioeng-062117-120924
|View full text |Cite
|
Sign up to set email alerts
|

Facet Joints of the Spine: Structure–Function Relationships, Problems and Treatments, and the Potential for Regeneration

Abstract: The zygapophysial joint, a diarthrodial joint commonly referred to as the facet joint, plays a pivotal role in back pain, a condition that has been a leading cause of global disability since 1990. Along with the intervertebral disc, the facet joint supports spinal motion and aids in spinal stability. Highly susceptible to early development of osteoarthritis, the facet is responsible for a significant amount of pain in the low-back, mid-back, and neck regions. Current noninvasive treatments cannot offer long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 165 publications
(183 reference statements)
1
59
0
4
Order By: Relevance
“…М. Attur и соавт. [ Тот факт, что у многих пациентов с хронической НБС боль отмечается в покое и ночью и уменьшается после разминки, то есть является воспалительной, может объясняться тем, что причиной ее появления часто становится ОА дугоотростчатых и крестцово-подвздошных суставов, а также остеит позвонков с формированием изменений по типу Modic I [30][31][32].…”
Section: фенотип скелетно-мышечной боли связанный с воспалением («воunclassified
See 1 more Smart Citation
“…М. Attur и соавт. [ Тот факт, что у многих пациентов с хронической НБС боль отмечается в покое и ночью и уменьшается после разминки, то есть является воспалительной, может объясняться тем, что причиной ее появления часто становится ОА дугоотростчатых и крестцово-подвздошных суставов, а также остеит позвонков с формированием изменений по типу Modic I [30][31][32].…”
Section: фенотип скелетно-мышечной боли связанный с воспалением («воunclassified
“…Не вызывает сомнений большое значение биомеханических нарушений и при развитии хронической НБС, особенно когда она связана с дегенеративными изменениями межпозвонковых дисков, а также ОА дугоотростчатых и крестцово-подвздошных суставов [30][31][32].…”
Section: фенотип скелетно-мышечной боли связанный с движением («мехаunclassified
“…To avoid assessing the same model used for different clinical scenarios, only original models (with model development presented for the first time) and their validation studies were included in this review. With its focus on methods and validation, this work is complementary to recent reviews on the role of each spinal component in load transmission (Ghezelbash et al 2020), on the structure-function relationship of the facet joints (O'Leary et al 2018), or on finite element analysis of the cervical spine biomechanics (Suarez-Escobar and Rendon-Velez 2018; Kim et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown association between intervertebral disc degeneration and facet osteoarthritis, even though the latter can exist without the former (Jaumard et al 2011b; Gellhorn et al 2013). Moreover, some disc treatments leading to adjacent disc disease are thought to exacerbate facet osteoarthritis (O'Leary et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Each pair of facet joints in lumbar spine has significant biomechanical contribution to stability and range of motion 5) . Disruption of the integrity of facet joint can lead to significant morbidity to the patient 15) . Fractures of lumbar spine posterior elements usually involved the pedicle or pars articularis.…”
Section: Introductionmentioning
confidence: 99%